Patient-Reported Outcomes After Corneal Transplantation. Issue 10 (October 2021) - Dunbar, Grace E.; Titus, Michael; Stein, Joshua D.; Meijome, Tomas E.; Mian, Shahzad I.; Woodward, Maria A.
Abstract : Purpose: To characterize vision-related quality of life after penetrating keratoplasty (PKP), deep anterior lamellar keratoplasty (DALK), Descemet stripping automated endothelial keratoplasty (DSAEK), and Descemet membrane endothelial keratoplasty (DMEK) using the National Eye Institute Visual Function Questionnaire (NEI-VFQ 9). Methods: Using the Sight Outcomes Research Collaborative ophthalmology electronic health record repository, questionnaire responses were obtained from 103 PKP patients, 24 DALK patients, 42 DSAEK patients, and 50 DMEK patients undergoing postoperative examination. No exclusions were made based on preoperative diagnosis, age, complications, or comorbidities. Associations between clinical characteristics and vision-related quality of life were analyzed using nonparametric and linear regression methods. Results: Patients were surveyed an average of 1.5 years postoperatively (range 24 d to 4.4 yrs). Participants who had undergone DALK, DMEK, DSAEK, and PKP had median composite VFQ scores of 77.8, 84.2, 76.1, and 70.6, respectively ( P = 0.002). There were no significant differences in VFQ scores between patients treated with DMEK versus DSAEK ( P = 0.440) or between patients treated with PKP versus DALK ( P = 1.000). Higher postoperative acuities in the operative and fellow eyes were associated with higher VFQ scores ( P < 0.001 and P < 0.001). When controlling for postoperative acuity by regression modeling, surgery type was not associated with patient-reported composite VFQ scores. Conclusions: In this study, patient-reported vision-related quality of life was similar among DMEK and DSAEK participants and also among DALK and PKP participants. When controlling for postoperative acuity, vision-related quality of life was similar among all study participants, irrespective of the keratoplasty technique. Abstract : Supplemental Digital Content is Available in the Text.